Spectral Analysis of Remote Sensing Data - A.Karam , Nihad; Razzaq , Ban Abdul; Mahdi , Afrah Salah (Iraqi Journal of Science, 2022)
In the present work, different remote sensing techniques have been used to analyze remote sensing data spectrally using ENVI software. The majority of algorithms used in the Spectral Processing can be organized as target detection, change detection and classification. In this paper several methods of target detection have been studied such as matched filter and constrained energy minimization.The water body mapping have been obtained and the results showed changes on the study area through the period 1995-2000. Also the results that obtained from applying constrained energy minimization were more accurate than other method comparing with the real situation.